Respons Agronomis dan Nutrisi Rumput Gama Umami terhadap Regimen Pupuk: Implikasi Sistem Pakan Ternak: Agronomic and Nutritional Responses of Gama Umami Grass to Fertilizer Regimens: Implications for Livestock Feeding Systems - Rezki Amalyadi (Agrocentrum, 2026)
Gama Umami grass (Pennisetum purpureum var. Gama Umami) is a superior forage grass that has the potential to support ruminant livestock productivity in tropical regions. The productivity and nutritional quality of this grass are greatly influenced by the fertilization strategy applied. This review article aims to synthesize empirical findings related to the agronomic and nutritional responses of Gama Umami grass to various fertilizer regimens and their implications in livestock feeding systems. This study was compiled based on an analysis of 44 scientific articles published in the last ten years and retrieved from reputable scientific databases. The review results show that inorganic fertilizers, especially nitrogen-based ones, consistently increase vegetative growth, biomass production, and crude protein content, but have the potential to cause nutrient imbalances and environmental impacts when used excessively. Organic and biological fertilizers make an important contribution to improving soil properties, microbial activity, and the sustainability of forage production systems, although yield increases tend to be more gradual. The integration of organic, inorganic, and bio fertilizers in an integrated fertilization regime has been proven to optimize the agronomic performance and nutritional quality of Gama Umami grass in a sustainable manner. These findings emphasize the importance of balanced and contextual fertilization management to improve the efficiency of tropical livestock feeding systems.